PENGARUH EARNING PER SHARE, CURRENT RATIO, STRUKTUR MODAL, RETURN ON EQUITY TERHADAP HARGA SAHAM PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lilie Lilie; Michael Michael; Triska Pramitha; Michelle Angela; Angelica Tiffany; Teng Sauh Hwee (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
The research objective is to test and analyze the effect of Earning Per Share, Current Ratio, Capital Structure, Return on Equity on stock prices on consumer goods companies listed on the Indonesia Stock Exchange. In this research using a population of 42 consumer goods companies listed on the Indonesia Stock Exchange for the 2013-2017 period with a sample of 24 consumer goods companies listed on the Indonesia Stock Exchange in the 2013-2017 period with a sample of 120 company financial report. This research was conducted by the classical assumption test with multiple linear regression research models. The results of this study are Earning Per Share and Return on Equity have an influence and significant effect on Stock Prices in consumer goods companies listed on the IDX Period 2013-2017. Current Ratio and Debt to Equity Ratio have no effect and significance on stock prices in consumer goods companies listed on the IDX for the 2013-2017 period. Earning Per Share (X1), Current Ratio (X2), Debt to Equity Ratio (X3), Return on Equity (X4) influence, and significant on Stock Prices in consumer goods companies that are listed on the IDX Period 2013-2017.